A local in time existence and uniqueness result of an inverse problem for the Kelvin-Voigt fluids. (22nd July 2021) - Kumar, Pardeep; Kinra, Kush; Mohan, Manil T
Abstract: In this paper, we consider an inverse problem for three dimensional viscoelastic fluid flow equations, which arises from the motion of Kelvin–Voigt fluids in bounded domains. This inverse problem aims to reconstruct the velocity and kernel of the memory term simultaneously, from the measurement described as an integral overdetermination condition. By using the contraction mapping principle in an appropriate space, a local in time existence and uniqueness result for the inverse problem of Kelvin–Voigt fluids are obtained. Furthermore, using similar arguments, a global in time existence and uniqueness result for an inverse problem for Oseen type equations are also achieved.